Numerical simulations of dynamic processes in the solar corona - Belov, Sofya (Jihočeská univerzita, 2022)
This master's thesis deals with 3D numerical simulations of turbulent flow past magnetic structures in the solar corona, focusing on the phenomenon of vortex shedding. This phenomenon is well known in hydrodynamic conditions. Still, it has not yet been satisfactorily investigated in magnetohydrodynamic (MHD) conditions, such as in the solar atmosphere, where its occurrence has been suggested by several studies and may explain some oscillatory phenomena. Numerical code Lare3d is used for the simulations.
Numerical simulations of dynamic processes in the solar corona
Keywords: vortex shedding; solar corona; coronal loops; solar prominences; coronal mass ejections; kink oscillations; magnetohydrodynamics; numerical simulations; Lare3d